Where is the line between benign and intrusive?, an examination of psychological barriers to the acceptance of awareness monitoring technologies - Zweig, David (University of Waterloo, 2001)
The rapid proliferation of communications technologies, designed to aid in information sharing and communications across distance, is changing the way people work. As employees find themselves in geographically separated teams, the loss of face=to=face interaction has led to the development of new monitoring technologies aimed at providing availability information to enhance collaboration. However, little attention has been paid to the psychological impact of these new types of monitoring technologies. This thesis presents three studies involving over 1200 participants examining the psychological effects of being monitored for availability. Drawing on diverse literatures in computer supported cooperative work, electronic performance monitoring, privacy and fairness, a comprehensive theoretical model of acceptance was developed to examine the effects of being monitored for availability. Studies 1 and 2 utilized a scenario design to assess participant reactions to a video-based monitoring system that provided availability information on geographically separated colleagues. Furthermore, Study 2 refined the model of acceptance to examine justifications provided to the employees for the use of awareness monitoring systems. The results of both studies suggested that technical solutions, such as manipulating the characteristics of the awareness system to enhance perceptions of fairness and privacy, are not sufficient to overcome psychological barriers to being monitored. Furthermore, perceptions of usefulness, considered to be a mediator in the relationship between fairness and privacy perceptions and acceptance, may indeed serve as a moderator of this relationship. A third study, using a focus group methodology, adds to the explanation for these findings. Specifically, the qualitative evidence suggests that maintaining psychological boundaries is a more important consideration than manipulating the technology to enhance perceptions of privacy and fairness. Furthermore, the premise behind the use of awareness monitoring might be faulty as awareness monitoring only provides information on a colleague's presence and not his or her availability to interact. Theoretical and practical implications for future research on technology acceptance and the design of new communications technologies are discussed.
Keywords: Harvested from Collections Canada